2014
DOI: 10.3389/fpsyg.2014.00934
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual spoken word training can promote or impede auditory-only perceptual learning: prelingually deafened adults with late-acquired cochlear implants versus normal hearing adults

Abstract: Training with audiovisual (AV) speech has been shown to promote auditory perceptual learning of vocoded acoustic speech by adults with normal hearing. In Experiment 1, we investigated whether AV speech promotes auditory-only (AO) perceptual learning in prelingually deafened adults with late-acquired cochlear implants. Participants were assigned to learn associations between spoken disyllabic C(=consonant)V(=vowel)CVC non-sense words and non-sense pictures (fribbles), under AV and then AO (AV-AO; or counter-bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 94 publications
6
35
1
Order By: Relevance
“…This principle was also demonstrated in Bernstein et al (2014, Exp. 1), in which prelingually deaf adults whose higher rank system for speech perception is vision received paired-associates training with the goal of improving unisensory auditory perception.…”
Section: Discussionsupporting
confidence: 73%
“…This principle was also demonstrated in Bernstein et al (2014, Exp. 1), in which prelingually deaf adults whose higher rank system for speech perception is vision received paired-associates training with the goal of improving unisensory auditory perception.…”
Section: Discussionsupporting
confidence: 73%
“…This further suggests, however, that the addition of vision plays a role in the auditory learning of some distinctions because the children tended to be better able to perceive more visible distinctions through AO with greater accuracy than those that are less visible. The cross-modal value of audition and vision in auditory learning is consistent with the findings of Bernstein et al (2014). Eisenberg et al (2003) have further suggested that vision may provide sensory assistance as the auditory cortex continues to adapt to auditory input.…”
Section: Table 5 Correlations Of the Mean Scores On Perception And Psupporting
confidence: 67%
“…These findings suggest that it might be beneficial to combine visual and auditory cues in the rehabilitation of the hearing impaired. However, audiovisual training appears to impede auditory speech learning in pre-lingually deaf individuals who receive cochlear implants later in life, presumably because of their greater dependence on visual speech perception than normalhearing subjects [87]. Nevertheless, a different result has been obtained in adult ferrets fitted with bilateral cochlear implants following deafening in infancy [14].…”
Section: Visual Influences On Auditory Spatial Plasticitymentioning
confidence: 99%